Impact monitor framework: development and implementation of a collaborative framework for aviation impact assessment - Alder, Marko; Ratei, Patrick; Riaz, Atif; Gupta, Utkarsh; Lefebvre, Thierry; Prakasha, Prajwal Shiva (MDPI, 2025)
The development and implementation of a collaborative framework for aviation impact assessment studies is presented. The focus is on which technologies can be used to enable the collaborative aspect, including the use of a common data model, the secure transfer of data between domain experts in different locations, and the automated execution of impact assessment workflows. It is demonstrated how the selected technologies can be extended to meet the requirements of air transport systems assessment and how they can be integrated into a common framework. The results of the developments are discussed in terms of their technical capabilities and the lessons learned from their practical use. The proposed framework shows that collaborative impact assessment studies can be conducted efficiently and securely. This forms the basis for three application studies in the same research project.
Keywords: framework; impact assessment; data model; remote execution; visualization